The emergence of multiculturalism in education: From ignorance to separation through recognition - Spajić-Vrkaš, Vedrana (Array, 2004)
The paper attempts to describe the changes in educational policy, theory and practice as the consequence of the recognition of cultural pluralism. The author points out the need to differentiate between cultural diversity and cultural pluralism and explains why the equation of these terms reflects an invalid thinking, especially in reference to a proper understanding of the way how scientific theory dealt with diversity in the past. To refer to unspeakable tragedies of, e.g., Saartjie Baartman and other “ savages" who were staffed and displayed for public in European museums until as recently as 1970s in terms of "inhumane" and "racist" acts means to uproot these acts from their historical, socio-cultural, political and scientific contexts in which they were perceived as normal human behaviour and not as social problematique mainly due to the authority of scientific ideologies, such as social Darwinism and functionalism. The shift towards cultural pluralism occurred in the middle of the second half of the 20th century as an answer to changes in cultural “ landscapes” of western societies caused by mass migrations and ethnic revitalisation movements. Although the changes were in the beginning perceived as the roots of social problems and explained according to a then dominant notion of cultural differences as social anomalies, it was more that obvious that such rationale was inconsistent with the principle of freedom and equality of all which was seen as the pillar of liberal democracies, as well as with an emerging international consensus reached by the Universal Declaration of Human Rights adopted in 1948 as "a common standard of achievement for all peoples and all nations". The impact of scientific ideologies on education is analysed in two phases, each comprising a variety of perspectives. In the pre-recognition phase, the author identifies three different approaches, namely the Golden Ages of Ignorance, the Disturbing Ages of Rhetoric and the Promising Ages of Accommodation, and goes on to explain why education was ignored as a means of change throughout that period. In the recognition phase, three new approaches to educational change are identified. The monocultural perspective, which is heavily influenced by Social Darwinism and the doctrine of modernisation, sees differences as a transitional quality and equates them with social anomaly. This approach is reflected in education in terms of request for equal integration of culturally different children into the mainstream culture. The multicultural perspective, which emerges with the acceptance of cultural pluralism, treats the differences as social reality. This approach, for which the author coins the term "ethnocentric multiculturalism", enters education through cultural retention policies and is often implemented in form of an isolated, stereotyped and past-oriented minority programme. The intercultural perspective sees the differences as social strength. The author argues here that multicultural and intercultural education may contribute to strengthening a culturally plural society only if cultural dialogue between and among different cultures were recognised, practiced and respected based on the principle of equal voices. Relying on some recent experiences of multicultural classes, she demonstrates in the end how education may fail to promote this objective and lead to new forms of separation if the dialogue is not conceptualised and practiced adequately, i.e. based on the principle of equal voices.